Emerging technologies in computing : first International Conference, iCETiC 2018, London, UK, August 23-24, 2018, Proceedings /: first International Conference, iCETiC 2018, London, UK, August 23-24, 2018, Proceedings. (2018) - Unknown
No abstract available